The Influence Of Discipline Development And Work Motivation On The Job Satisfaction Of CV Employees. Bladas.Co - Mutiya Kansa M; Indrajati Wibowo (Sean Institute, 2024)
employees . Bladas.co has level high absenteeism . This matter indicated level satisfaction low work . Besides that enhancement absenteeism can showing exists decline discipline employee so that required coaching discipline and motivation nice work . Study This done For know influence coaching discipline and motivation Work to satisfaction Work CV employees . Bladas.co is good in a way Partial nor simultaneous. Deep method study This use method study Quantitative, techniques data collection uses Questionnaire . Respondent in study This that is all population units that is CV employees . Bladas.co, numbering 36. Analysis study This use multiple linear regression and determination . Tools used in research namely SPSS version 25. Research results This showing in a way Partial coaching discipline and motivation to satisfaction Work CV employees . Bladas.co is influential positive . By simultaneous , coaching discipline and motivation Work influential to satisfaction Work CV employees . Bladas.co.